2017
DOI: 10.3389/fphar.2017.00058
|View full text |Cite
|
Sign up to set email alerts
|

Post-operative Bleeding Risk in Dental Surgery for Patients on Oral Anticoagulant Therapy: A Meta-analysis of Observational Studies

Abstract: Background and Objective: Minor dental surgery is invasive and hemorrhagic. Thus, in patients treated with anticoagulants, the bleeding risk related to these invasive procedures is concerning. The aim of this meta-analysis is to evaluate this risk by comparing the post-operative bleeding rates of oral anticoagulation treatment (OAT) patients (without interrupted or altered anticoagulant intake) with non-OAT patients.Methods: PubMed, Embase and the Cochrane Library were searched for eligible studies that compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
30
0
12

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 49 publications
1
30
0
12
Order By: Relevance
“…In patients taking oral anticoagulant therapy (vitamin-K antagonists, VKA) and undergoing dental extraction, minor dental procedures and dental implant placement do not seem to increase the risk of bleeding compared to patients who discontinue oral anticoagulant therapy [118,139]. There may be a higher postoperative bleeding risk in patients continuing VKA and undergoing either minor dental surgery or other higher-risk procedures when compared to non-VKA patients [10,118], but local haemostatic agents appear to be effective in controlling post-operative bleeding [72].…”
Section: Vitamin-k Antagonistsmentioning
confidence: 99%
“…In patients taking oral anticoagulant therapy (vitamin-K antagonists, VKA) and undergoing dental extraction, minor dental procedures and dental implant placement do not seem to increase the risk of bleeding compared to patients who discontinue oral anticoagulant therapy [118,139]. There may be a higher postoperative bleeding risk in patients continuing VKA and undergoing either minor dental surgery or other higher-risk procedures when compared to non-VKA patients [10,118], but local haemostatic agents appear to be effective in controlling post-operative bleeding [72].…”
Section: Vitamin-k Antagonistsmentioning
confidence: 99%
“…The newsletter article mentions that the physician may recommend interrupting anticoagulation (either warfarin or direct anticoagulation) for dental procedures, but there is overwhelming evidence that dental surgery is safe in these patients and that interrupting anticoagulation increases the risk of a possibly fatal or permanently debilitating embolic complication. At least 10 systematic reviews [3][4][5][6][7][8][9][10][11][12] and at least 7 national medical or dental group statements from 9 national medical or dental groups (including the American Dental Association) have concluded that dental surgery can be safely performed without interrupting anticoagulation therapy. [12][13][14][15][16][17][18] Numerous prospective studies have reached the same conclusion.…”
Section: Is It Rude To Interrupt?mentioning
confidence: 99%
“…24 The reason for the higher recommended therapeutic range for anticoagulation is that these patients are at higher risk of stroke compared with most other patients. There is voluminous literature, including the aforementioned 10 systematic reviews [3][4][5][6][7][8][9][10][11][12] and at least 7 national medical or dental group statements from 9 national medical or dental groups (including the American Dental Association), confirming that dental surgery can be safely performed at therapeutic levels-up to and even higher than INR 3.5. [12][13][14][15][16][17][18] By instructing not to treat if INR is above 3, dentists (in consultation with physicians) may wrongly advise their patients with the highest embolic risk (patients with mechanical mitral valves) to interrupt and/or reduce their anticoagulation for dental surgery, increasing their risk of embolic complications.…”
Section: Do Not Treat If Inr Above 3?mentioning
confidence: 99%
“…322/327 INTRODUÇÃO Diante do envelhecimento populacional e do aumento da expectativa de vida, a incidência de doenças crônicas, como cardiopatias e desordens vasculares, é cada vez mais comum 1,2 . De modo a prevenir futuros eventos tromboembólicos, o uso de antiagregantes plaquetários e anticoagulantes orais são amplamente utilizados na profilaxia e no tratamento destas doenças [1][2][3] . Consequentemente, o número de pessoas que necessitam de tratamento odontológico e fazem uso de anticoagulantes é crescente.…”
unclassified
“…No passado, muitos dentistas indicavam a suspensão de anticoagulantes previamente a procedimentos odontológicos invasivos, a fim de reduzir o risco de sangramento 3,4 . Mas, atualmente, já se entende que, caso o procedimento odontológico a ser realizado seja considerado de menor magnitude e com baixo risco de sangramento, a suspensão dos anticoagulantes previamente ao procedimento é desnecessária 2,4,[5][6][7] . Na maioria das vezes, o sangramento pós-operatório não é exclusivamente atribuído ao uso de antiagregantes plaquetários 8 ou anticoagulantes orais 2,5 , quando medidas hemostáticas locais são corretamente adotadas.…”
unclassified